Sistem Proteksi Manajemen Daya Ruang Simpan Stok Ikan Berbasis IOT di CV. Indonesia Nature Miracle - kridoyono, agung; Harton, Elvianto Dwi; Yunanda, Anton Breva; Sidqon, Mochamad; Sudaryanto, Aris (Journal of Science and Social Development, 2023)
This article is a community service journal as a form of activity report in the implementation of higher education tridharma activities. This service is the application of IOT in the placement and classification of fish quality. The circulation model and selection of quality fish are only given a place and a label so that it allows the misuse of fish by related parties, either repacking or selling actions that do not comply with company standards. In solving problems with the company, we provide service in the form of making prototypes of fish placement media and supervision in the form of direct monitoring to superiors through cloud control by obtaining information on recording the date of entry and exit of fish from the container and also the name of the person in charge of Quality control, so that it can be used to support quality fish and also to maintain the availability of these fish. In this system, informants are determined based on an implementation study, namely the company management. Analysis and mitigation of supply chain risk has an impact on sales and inventory, with the existence of this program it is hoped that it can assist companies in implementing product quality determination. Keywords: website, Supply chain, klasifikasi stok ikan